White matter microstructure contributes to age-related declines in task-induced deactivation of the default mode network - Brown, Christopher A.; Hakun, Jonathan G.; Zhu, Zude; Johnson, Nathan F.; Gold, Brian T. (Frontiers in Aging Neuroscience, 2015)
Task-induced deactivations within the brain’s default mode network (DMN) are thought to reflect suppression of endogenous thought processes to support exogenous goal-directed task processes. Older adults are known to show reductions in deactivation of the DMN compared to younger adults. However, little is understood about the mechanisms contributing to functional dysregulation of the DMN in aging. Here, we explored the relationships between functional modulation of the DMN and age, task performance and white matter (WM) microstructure. Participants were 117 adults ranging from 25 to 83 years old who completed an fMRI task switching paradigm, including easy (single) and difficult (mixed) conditions, and underwent diffusion tensor imaging (DTI). The fMRI results revealed an age by condition interaction (β = -.13, t = 3.16, p = .002) such that increasing age affected deactivation magnitude during the mixed condition (β = -.29, t = -3.24 p = .002) but not the single condition (p = .58). Additionally, there was a white matter by condition interaction (β = .10, t = 2.33, p = .02) such that decreasing white matter microstructure affected deactivation magnitude during the mixed condition (β = .30, t = 3.42 p = .001) but not the single condition (p = .17). Critically, mediation analyses indicated that age-related reductions in WM microstructure accounted for the relationship between age and DMN deactivation in the more difficult mixed condition. These findings suggest that age-related declines in anatomical connectivity between DMN regions contribute to functional dysregulation within the DMN in older adults.